New Data on Hill-forts of North-Western Latvia - Vasks, Andrejs (Archaeologia Lituana, 2011)
There are some 470 hill-forts in Latvia, 80 of which have seen large- or small-scale excavation (Vasks, 2005, p. 38–42). The majority of these 80 hill-forts are located in eastern Latvia, and only nine have been excavated in the western part of the country. Out of these nine, only Talsi Hill-Fort has been excavated on a large scale, while the rest have been subject only to limited excavation. Accordingly, archaeological research in western Latvia, including hill-fort research, has been given greater attention in recent years. Since 2002 the Department of Archaeology and Ancillary Historical Sciences of the University of Latvia has organised the excavation of several archaeological sites in western Latvia in the frame of student field courses. The excavated sites include three hill-forts: Beltes, Mežīte and Puze (Fig. 1). [...]